2014
DOI: 10.1093/eurpub/cku101
|View full text |Cite
|
Sign up to set email alerts
|

Recent research on the mental health of immigrants to Sweden: a literature review

Abstract: Immigrants to Sweden are a mixed group with differing, but often increased, risks of mental disorders. Targeted qualitative and intervention studies may facilitate efforts to develop and implement preventive methods for immigrants at high risk of mental ill health, and to tailor treatment to the specific needs of different immigrant groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 73 publications
9
77
0
Order By: Relevance
“…A literature review concludes that mental health is poorer in foreign-born populations, with a higher prevalence of depressive symptoms, and that migrants from refugee countries had a higher prevalence of anxiety than native Swedes (Gilliver et al, 2014). These findings are in line with those of our study.…”
Section: Discussionsupporting
confidence: 92%
“…A literature review concludes that mental health is poorer in foreign-born populations, with a higher prevalence of depressive symptoms, and that migrants from refugee countries had a higher prevalence of anxiety than native Swedes (Gilliver et al, 2014). These findings are in line with those of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous European findings of higher incidence of tuberculosis among immigrants compared to native-born were also found in Denmark [51]. Consistent with European findings on mental health [52,53] as well as self-perceived health [54] the review also showed both poorer mental health and self-perceived health among immigrants compared to native-born. Self-reported health among immigrant children seem also to be comparable to Swedish findings [55].…”
Section: Discussionsupporting
confidence: 85%
“…Although our findings do not support the ethnic density hypothesis, we note that every immigration experience is unique (e.g., social norms, cultural customs, and resources of the immigrant group; the migration and acculturation process, including experiences of discrimination; and the norms, customs, and economic status of the host nation), and thus it is not surprising that findings regarding the relationship between ethnic density and mental health are mixed. We also note that the immigrants in our sample had higher cumulative incidence of affective disorders but not non-affective psychosis relative to the native-born population; this is consistent with other research showing that the cumulative experience of pre-migration stressors, the migration experience itself, and exposure to stressors after arriving in the host country, including experiences of discrimination, are important determinants of stress-related psychopathology such as affective disorders for immigrants (Tinghög et al, 2007; Tinghög et al, 2010; Veling & Susser, 2011; Gilliver et al, 2014). …”
Section: Discussionsupporting
confidence: 91%